ACCURACY OF SYSTEMIC INFLAMMATORY IMMUNE INDEX (SII) IN ASSESSING MYASTHENIA GRAVIS SEVERITY - DR MUHAMMAD FAHAD , DR AYESHA ASLAM , DR ALI EJAZ , DR MAHRUKH LIAQAT , DR ABDUL WAHAB , DR TAYYAB HASNAIN (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Objective: To determine the accuracy of systemic inflammatory immune index in assessing myasthenia gravis severity using MGFA classification as gold standard. Study Design: Descriptive cross-sectional study. Place And Duration Of Study: Neurology department of Mayo Hospital Lahore from June 2025 to September 2025. Methodology: This study was done after taking ethical approval from IRB. This study was done on 178 patients diagnosed with MG, recruited from Neurology and Medicine department. Data collection was done using pre-designed proforma. Prior to enrollment written consent was obtained from patients. Blood samples were collected prior to treatment, and SII was calculated (>1105.412 was considered as elevated) and MGFA IV & V was considered as severe MG. Data were analyzed using SPSS v26, and diagnostic performance metrics were calculated. Results: Mean age was 37.12 ± 7.80 years, with 68% females. MGFA classification identified 24.2% severe cases, mean SII was 878.71 ± 237.16, and 23.6% exhibiting raised values. Sensitivity, specificity and accuracy of SII for predicting severe MG were 88.37%, 97.04%, and 94.94%. Subgroup analysis showed consistent diagnostic performance: accuracy was 95.92% in patients ≤30 years and 94.57% in those >30 years, 95.87% in females versus 92.98% in males, and sensitivity was higher in patients with MG-ADL >12 (90%) compared to those with MG-ADL ≤12 (66.67%). Conclusion: The study demonstrates that systemic immune-inflammation index is highly accurate biomarker for identifying severe myasthenia gravis. These findings suggest that SII could be a valuable tool for early risk stratification and clinical decision-making in patients with myasthenia gravis.